America firsthand - Marcus, Robert D., 1936-; Burner, David, 1937-; Marcus, Anthony, 1963- (Boston : Bedford/St. Martin's, 2004)
Presents history in the words of the people who made it, inviting and provoking students to think critically about the past. The seventh edition continues to bring the past to life with more visual and textual sources that increase diversity, represent current scholarship, and engage students.
v. 1. Readings from settlement to Reconstruction -- v. 2. Readings from Reconstruction to the present.
Includes bibliographical references.
Keywords: United States -- History -- Sources; United States; History; Sources